Syrian Refugees and the Digital Passage to Europe: Smartphone Infrastructures and Affordances. (March 2018) - Gillespie, Marie; Osseiran, Souad; Cheesman, Margie
This research examines the role of smartphones in refugees' journeys. It traces the risks and possibilities afforded by smartphones for facilitating information, communication, and migration flows in the digital passage to Europe. For the Syrian and Iraqi refugee respondents in this France-based qualitative study, smartphones are lifelines, as important as water and food. They afford the planning, navigation, and documentation of journeys, enabling regular contact with family, friends, smugglers, and those who help them. However, refugees are simultaneously exposed to new forms of exploitation and surveillance with smartphones as migrations are financialised by smugglers and criminalized by European policies, and the digital passage is dependent on a contingent range of sociotechnical and material assemblages. Through an infrastructural lens, we capture the dialectical dynamics of opportunity and vulnerability, and the forms of resilience and solidarity, that arise as forced migration and digital connectivity coincide.